Production of bacterial endoglucanase from pretreated oil palm empty fruit bunch by bacillus pumilus EB3 - Ariffin, Hidayah; Hassan, Mohd Ali; Md Shah, Umi Kalsom; Abdullah, Norhafizah; Mohamad Ghazali, Farinazleen; Shirai, Yoshihito (Elsevier, 2008)

(untitled)
In this study, endoglucanase was produced from oil palm empty fruit bunch (OPEFB) by a locally isolated aerobic bacterium, Bacillus pumilus EB3. The effects of the fermentation parameters such as initial pH, temperature, and nitrogen source on the endoglucanase production were studied using carboxymethyl cellulose (CMC) as the carbon source. Endoglucanase from B. pumilus EB3 was maximally secreted at 37°C, initial pH 7.0 with 10 g/l of CMC as carbon source, and 2 g/l of yeast extract as organic nitrogen source. The activity recorded during the fermentation was 0.076 U/ml. The productivity of the enzyme increased twofold when 2 g/l of yeast extract was used as the organic nitrogen supplement as compared to the non-supplemented medium. An interesting finding from this study is that pretreated OPEFB medium showed comparable results to CMC medium in terms of enzyme production with an activity of 0.063 U/ml. As OPEFB is an abundant solid waste at palm oil mills, it has the potential of acting as a substrate in cellulase production.